Aiding Imperiled Fish and Mussel Conservation Using Swimming Performance Metrics to Inform the Design or Modification of Road Stream Crossings - Allie N. Burdette-Lapuz; Malachi R. Hubbard; Cameron M. Emadi; Preston T. Bean; Edward M. Mager (Fishes, 2026)
Culvert construction at stream crossing sites can lead to zones of high-velocity water flow which can disrupt the dispersal and connectivity of species of greatest conservation need (SGCN) in Texas. To help inform effective culvert design, the swimming performance of the following seven fish species has been measured, the first three of which are SGCN themselves, and the last four serve as hosts for glochidia of SGCN mussels (mussel genera indicated in parentheses): Colorado Roundnose Minnow, Texas Shiner, Headwater Catfish, Largemouth Bass (host for Lampsilis spp.), Green Sunfish (host for Lampsilis spp.), Channel Catfish (host for Cyclonaias spp.) and Blacktail Shiner (host for Fusconaia spp.). The primary objective was to measure the critical swimming speeds (Ucrit) under a range of relevant temperatures (15, 22.5, and 30 °C) to be used in site-specific calculations of culvert water velocities (Vf). A secondary objective was to collect additional physiological endpoints of relevance to overall swimming performance, including maximum burst swimming speed (Umax), metabolic rate measurements (i.e., standard (SMR), maximum (MMR) and aerobic scope (AS)) and calculations of cost of transport (COT) and optimal swimming speed (Uopt). As expected, Ucrit tended to increase with increasing temperature for several species with metabolic rate measurements following congruent trends, whereas Umax exhibited thermal independence for all species.